Yukio Mishima, “Tumultul valurilor” [Yukio Mishima, “The Sound of Waves”] - Lucian Vasile Bâgiu (Incursiuni în imaginar)
The essay aims at decoding the 1954 novel The Sound of Waves in relation to Mishima’s biography, political and aesthetic theory, arguing that his most serene artistic achievement is, in the end, a desperate self-deluding for various inner contradictions. In a minute hermeneutic approach the article identifies and interprets such defining issues as: suicide, loneliness, individualism, egoism, materialism, decisive action, physical strength, traditionalism, religiosity, providence, knowledge, experience, love, capitulation, etc. The essay proves that, beyond an apparent thin shell of delightful fairy-tale like realm and story, The Sound of Waves is but a show of failed art therapy for the nightmarish inner universe of an idealist.